Problem-based learning for developing students’ critical thinking skills in human digestive system learning - Suherni Suherni; Elya Nusantari; Masra Latjompoh; Pricillia Putri Wiratami Minggu; Sri Rahayung Nusi; Merlin Tombo; Tri Vinesa Moha (Universitas Papua, 2026)
This research seeks to evaluate the implementation of the Problem-Based Learning (PBL) to enhance students' critical thinking skills about the human digestive system content. This study method is pre-experimental, using a one-group pretest-posttest design. The research sample comprised 100 students, 45 males and 55 females, all in grade VIII at junior high schools in South Bolaang Mongondow Regency. Data-gathering methods included tests and questionnaires using the Guttman scale. The paired-samples t-test was used to see whether there was a significant difference between students' pretest and posttest results after PBL education. The data analysis indicated that the implementation of PBL significantly enhanced students' critical thinking (Sig. < 0.05). The N-Gain calculation result of 0.70 falls into the high category. The implementation of learning was assessed as good to very good, while students' answers to PBL were evaluated as very good. The results suggest that PBL is a pertinent and effective method for fostering critical thinking in junior high school science education, especially in contextual subjects closely linked to students' daily experiences.